Kandidiasis Vulvovaginalis dalam Kehamilan Gemeli - Sofvina, Winda; Adawiyah, Robiatul; Inawaty, Inawaty; Amalia, Nurul; Wahdini, Sri (Fakultas Kedokteran Universitas Riau, 2024)
Vulvovaginitis is inflammation of the vulva and vagina caused by Candida spp, bacteria, and Trichomonas vaginalis. Clinical symptoms of vulvovaginitis include itching, burning, and vaginal discharge. Many women buy over-the-counter drugs and treat themselves without knowing the cause of their vulvovaginitis, so the treatment they get is not optimal, therefore, an examination is needed to determine the organism causing the vulvovaginitis. This case report was made to know the cause of vulvovaginitis in a patient. A 25-year-old woman came with complaints of odorless yellowish-white vaginal discharge, complaints accompanied by itching, and dysuria. The patient is pregnant with a gestational age of 28-29 weeks. On physical examination, the vulva appears reddish, vaginal discharge is yellowish-white. On direct microscopic examination, yeast cells and pseudohyphae were found. Culture on SDA+ agar produced colonies of Candida sp.